Impulsive-Integral Inequalities for Attracting and Quasi-Invariant Sets of Neutral Stochastic Integrodifferential Equations with Impulsive Effects - Ramkumar, K.; Anguraj, A. (Journal of Applied Nonlinear Dynamics, 2026)
In this article, we investigate a class of neutral stochastic integrodifferential equations with impulsive effects. The results are obtained by using the new integral inequalities, the attracting and quasi-invariant sets combined with theories of resolvent operators. Moreover, exponential stability of the mild solution is established with sufficient conditions. An example is provided to illustrate the results of this work.